Influenza A H1N1 induces declines in alveolar gas exchange in mice consistent with rapid post‐infection progression from acute lung injury to ARDS. Issue 3 (2nd August 2012) - Traylor, Zachary P.; Aeffner, Famke; Davis, Ian C.
<x xml:space="preserve">Abstract</x> Background Patients with severe seasonal or pandemic influenza pneumonia frequently develop acute respiratory distress syndrome (ARDS). One clinical diagnostic criterion for ARDS is the PaO2:FiO2 ratio, which is an index of alveolar gas exchange. However, effects of H1N1 influenza infection on PaO2:FiO2 ratios and related pathophysiologic readouts of lung function have not been reported in mice. Methods To develop a method for determining PaO2:FiO2 ratios, uninfected mice were anesthetized with pentobarbital, diazepam/ketamine, or inhaled isoflurane. Subsequently, they were allowed to breathe spontaneously or were mechanically ventilated. After 15 minutes exposure to room air (FiO2 = 0·21) or 100% O2 (FiO2 = 1·0), carotid PaO2 was measured. To determine influenza effects on PaO2:FiO2, mice were challenged with 10 000 p.f..u./mouse influenza A/WSN/33. Results PaO2:FiO2 ratios were abnormally low (≤400 mmHg) in spontaneously breathing mice. Mechanical ventilation with positive end‐expiratory pressure was required to obtain PaO2:FiO2 ratios in uninfected mice consistent with normal values in humans (≥600 mmHg). At day 2 following infection PaO2:FiO2 ratios indicated the onset of acute lung injury. By day 6, PaO2:FiO2 ratios were <200 mmHg, indicating progression to ARDS. Impaired gas exchange in influenza‐infected mice was accompanied by progressive hemoglobin desaturation, hypercapnia, uncompensated respiratory acidosis, hyperkalemia, and polycythemia. Conclusions Influenza infection of mice results in impairment of alveolar gas exchange consistent with rapid development of acute lung injury and progression to ARDS. PaO2:FiO2 ratios may be of utility as clinically relevant and predictive outcome measures in influenza pathogenesis and treatment studies that use mouse models.